Perception of undergraduate medical students regarding civic responsibility through service learning by visiting persons with different abilities - Sajida Naseem, Syeda Hanaa Fatima, Saima Rafi, Lubna Meraj, (Journal of Rawalpindi Medical College, 2022)
Objectives: Addressing various attitudes of students, can be a challenging task for educationists, so it is generally embedded in the hidden curriculum in most Medical Institutes. The purpose of this study was to build up civic duty among undergraduates, rooted in their learning objectives of the curriculum through a visit to the school of children with different abilities (CFSPF). Materials and Methods: In year 4, students of Shifa College of Medicine during the clerkship of Community Medicine, were taken on a field visit which is part of the curriculum. CFSP is privately run by an NGO, it has 45 enrolled individuals with different mental and physical abilities. The medical students visited CFSPF in small groups for 8 months (Sep 2019 to April 2020) where they interacted with the individuals with special needs in their environment. Students were able to practice empathy through the general physical examination and other entertaining activities. In this qualitative study, this strategy was assessed by exploring the medical student’s perceptions. Results: Focus Group discussions were conducted with the medical students and themes identified were: interaction with children having different abilities, being thankful to the Almighty, philanthropy, learning to empathize, the feeling of including them in our society, selfless smile, the contribution of services, and developing various attributes. Conclusion: Students found the visit to a school for children with different abilities useful. The interaction in a different environment has revealed opportunities for a wider scope of learning. Keywords: Civic responsibility, Empathy, Persons with different abilities, Service learning.